Funny story - Henry, Emily (Berkley, 2024)
"A shimmering, joyful new novel about a pair of opposites with the wrong thing in common, from #1 New York Times bestselling author Emily Henry, Daphne always loved the way Peter told their story. How they met, fell in love, and moved back to his lakeside hometown to begin their life together. Too bad it turned out to be more of a prequel, a complication to Peter's actual love story, the one that ends with him dumping Daphne before their wedding to begin a relationship with his lifelong best friend, Petra. And so that's how Daphne's story really begins: stranded in beautiful Waning Bay, Michigan, without friends or family but with a dream job as a children's librarian (that barely pays the bills), and proposing to be roommates with the only other non-Peter-related person she knows: Petra's heartbroken ex, Miles Nowak. Just until she can get a new dream job literally anywhere else. Scruffy and chaotic, Miles is entirely the opposite of buttoned-up Daphne, and they mainly avoid one another until one night, while drowning their sorrows, they form a tenuous friendship. Miles decides he will convince Daphne to give Waning Bay a real shot. He'll show her why he loves this idyllic town and its residents, and if they happen to post deliberately misleading photos of their adventures together--for a particular audience of two--who could blame them? Miles believes Daphne deserves the chance to build a life here, her own life. As she begins to fall for the town, Daphne wonders what this summer is supposed to mean. Is it just for fun? An interlude to her own love story? Or maybe it was never meant to be a love story? Maybe it was just an anecdote to share at future dinner parties: that time she fell in love with her ex-fiancé's new fiancée's ex-boyfriend. Who's to say?"--